Method for promoting reduction of electrocatalytic nitrogen to synthesize ammonia based on MnC60 heterojunction built-in electric field
By designing the built-in electric field of MnC60 heterojunction, the problems of N2 adsorption and N≡N bond cleavage in electrocatalytic nitrogen reduction reaction are solved, and efficient electrochemical ammonia synthesis is achieved, and the yield and efficiency are significantly improved.
Patent Information
- Application Number
- CN202411674810.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The main problem of existing electrocatalytic nitrogen reduction reactions (eNRR) is N2 adsorption and N≡N bond cleavage, and the performance of the electrocatalyst is not sufficient to meet the requirements of practical applications.
By designing the MnC60 heterojunction, the built-in electric field is used to promote electron transfer and reactant diffusion, thereby accelerating the nitrogen reduction reaction. The method includes material preparation, preparation of Mn/C60 heterostructure, performance testing of electrocatalytic nitrogen reduction reactions, and density functional theory calculation and analysis.
High-efficiency electrochemical ammonia synthesis at room temperature and pressure was achieved. The Faraday efficiency of Mn/C60 catalyst at -0.4V to RHE reached 42.18%, and the NH3 yield was 14.52μgh-1mgcat-1.
Smart Images

Figure CN119506938A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrochemical nitrogen reduction reaction, and in particular to a method for synthesizing ammonia by promoting electrocatalytic nitrogen reduction based on a built-in electric field of a MnC60 heterojunction. Background Art
[0002] Ammonia is an indispensable substance in agriculture and industry, used in large-scale fertilizer production and supporting various chemical processes. Its high concentration of hydrogen and carbon-free properties make it a promising energy carrier for sustainable energy solutions and climate change mitigation. The large-scale synthesis of NH3 began with the Haber-Bosch process in the early 20th century, which is a thermodynamically exothermic and spontaneous reaction. Due to the strong bond energy of the N≡N triple bond (940.95 kJmol-1) and the huge energy barrier (410 kJmol-1) in the first step of the dissociation of the N≡N triple bond, the reaction requires high temperature (350℃-450℃) to accelerate the reaction rate, and high pressure (100-200bar) to ensure a forward reaction according to Le Chatelier's principle.
[0003] However, the Haber-Bosch process is not only energy-intensive but also produces a large amount of greenhouse gases (mainly CO2) during the steam methane reforming (SMR) process to produce H2. Recently, electrocatalytic nitrogen reduction reaction (NRR) in water-based electrolytes powered by renewable energy such as wind and solar energy has provided a promising alternative to the Haber-Bosch process for efficient synthesis of NH3. However, the main problems of the electrocatalytic nitrogen reduction reaction (eNRR) are N2 adsorption and N≡N bond cleavage, which are closely related to the composition and structure of the electrocatalyst.
[0004] To date, researchers have proposed several approaches to design catalysts to enhance N2 adsorption and activation of inert N≡N triple bonds. Defect engineering and heteroatom doping have long been considered as effective strategies to tune the surface electronic structure of electrocatalysts through surface electron redistribution to optimize N2 adsorption. However, the performance of NRR electrocatalysts is still insufficient to meet the requirements of practical applications, and the underlying mechanism is not yet fully understood.
[0005] Designing heterojunctions to construct built-in electric fields is considered an effective strategy to improve electrocatalytic activity, which can accelerate reaction kinetics by promoting electron transfer and reactant diffusion. The work function difference between the two materials in the heterojunction induces interface polarization, generates a potential difference, and promotes the spontaneous movement of electrons near the interface, eventually forming local electron-rich and positively charged regions, forming a charge distribution gradient, and establishing a built-in electric field. This built-in electric field can promote electron transfer and regulate the charge density around the active sites, thereby improving the intrinsic activity of the electrocatalyst.
[0006] In view of this, a method for synthesizing ammonia by promoting electrocatalytic nitrogen reduction based on a built-in electric field of a MnC60 heterojunction is provided to overcome the above problems. Summary of the invention
[0007] The object of the present invention is to provide a method for synthesizing ammonia by promoting electrocatalytic nitrogen reduction based on a built-in electric field of a MnC60 heterojunction, so as to solve the problems raised in the above-mentioned background technology.
[0008] In order to solve the above technical problems, the present invention provides a method for synthesizing ammonia by promoting electrocatalytic nitrogen reduction based on a built-in electric field of a MnC60 heterojunction, comprising the following steps:
[0009] S1. Material preparation, including buckminsterfullerene, carbonyl manganese, disodium hydrogen phosphate dihydrate, acetone, salicylic acid, sodium citrate, sodium hypochlorite, sodium nitroferricyanide dihydrate, sodium hydroxide, ammonium chloride, Nafion membrane 211, ethanol, and purified water;
[0010] Preparation of S2, Mn / C60 heterostructures:
[0011] Take Mn2(CO)10 (20 mg) and C60 (80 mg) and put them into an agate mortar;
[0012] Grind in a mortar for 30 minutes to thoroughly mix the two substances;
[0013] The ground mixture was placed in an argon environment and heated to 300 °C at a heating rate of 5 °C / min;
[0014] Annealing treatment was performed at 300°C for 1 hour;
[0015] After annealing, the sample was allowed to cool naturally to room temperature to obtain the Mn / C60 sample;
[0016] S3. Preparation of comparative materials, including preparation of metal Mn nanoparticles and preparation of C60;
[0017] S4, electrocatalytic nitrogen reduction reaction performance test;
[0018] S5. Density functional theory calculation and analysis.
[0019] Further, in S3, the preparation of metal Mn nanoparticles comprises the following steps:
[0020] Take Mn2(CO)10 (40 mg), mix well and put into a porcelain boat for heating;
[0021] Metallic Mn nanoparticles were synthesized through the same annealing and post-treatment process as that of synthesizing Mn / C60.
[0022] Further, in S3, the preparation of C60 comprises the following steps:
[0023] Take 40 mg of C60, mix well and put into a porcelain boat for heating;
[0024] The same annealing and post-treatment process as that of Mn / C60 synthesis was performed.
[0025] Furthermore, in S4, the following steps are included:
[0026] Prepare 0.08M Na2HPO4 solution as electrolyte;
[0027] The prepared Mn / C60 sample was used as a working electrode to form an electrochemical cell with a counter electrode and a reference electrode.
[0028] Furthermore, in S4, the following steps are also included:
[0029] In the electrochemical cell, a voltage of -0.4 V was applied to the working electrode;
[0030] During the reaction process, the current changes in the circuit are detected in real time to reflect the progress of the electrocatalytic reaction;
[0031] The amount of NH3 generated was quantitatively detected.
[0032] Furthermore, the method further comprises the following steps:
[0033] S6. Characterization analysis; including scanning electron microscopy, high-resolution transmission electron microscopy and energy spectrum analysis.
[0034] Furthermore, in the SEM analysis:
[0035] The synthesized Mn / C60 and C60 were analyzed by scanning electron microscopy; the scanning electron microscope images of the synthesized (ab)Mn / C60 and (cd)C60 were observed to obtain the surface morphology, particle size and distribution of the materials; the influence of the formation of heterogeneous structure on the surface properties of the material was studied by comparing the differences in microstructure between the Mn / C60 heterostructure and pure C60; and it was correlated with the electrocatalytic performance.
[0036] Furthermore, in high-resolution transmission electron microscopy and energy dispersive spectroscopy analysis:
[0037] High-resolution transmission electron microscopy analysis of the synthesized C60;
[0038] At the same time, combined with the EDS spectrum (df), the elemental composition and distribution of C60 were analyzed.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] The Mn / C60 heterostructure obtained by this method through simple grinding and low-temperature (300℃) annealing process shows excellent electrocatalytic activity in the process of electrocatalytic conversion of N2 to NH3 under ambient conditions. The prepared Mn / C60 has a FE value of up to 42.18% and an NH3 yield of up to 14.52μgh-1mgcat-1 at a voltage of -0.4V compared with RHE in 0.08MNa2HPO4 solution. A series of characterization techniques, electrochemical tests and theoretical calculations show that.
[0041] The built-in electric field of the Mn / C60 heterojunction promotes the redistribution of local charges, resulting in obvious nucleophilic and electrophilic sites on the Mn / C60 surface, which can effectively enhance the adsorption of N2.
[0042] The formation of space charge regions in the Mn / C60 heterostructure helps accelerate the electrocatalytic kinetics, making the N2 adsorption step a thermodynamically favorable process (-0.35 eV) and reducing the energy barrier of the rate-determining step (*N─NH2+H++e-→*N, ΔG=0.57 eV). This indicates that designing electrocatalysts by designing and constructing heterostructures is a feasible strategy for the electrocatalytic nitrogen reduction reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The scanning electron microscope images of Mn / C60 and C60 synthesized in the method for synthesizing ammonia by promoting electrocatalytic nitrogen reduction based on the built-in electric field of MnC60 heterojunction of the present invention are shown;
[0044] Figure 2 A high-resolution transmission electron microscope image of synthesized C60 and an EDS image of C60 in a method for synthesizing ammonia by promoting electrocatalytic nitrogen reduction based on a built-in electric field of a MnC60 heterojunction according to the present invention;
[0045] Figure 3 This is a comparison diagram of the electrocatalytic activity of Mn / C60 in producing NH3 through NRR in a method for synthesizing ammonia by electrocatalytic nitrogen reduction promoted by a built-in electric field based on a MnC60 heterojunction of the present invention and previously reported NRR electrocatalysts. DETAILED DESCRIPTION
[0046] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0047] See also Figure 1-Figure 3 , the present invention provides a technical solution:
[0048] See also Figure 1-Figure 3 As shown, ( Figure 1 Scanning electron microscope images of synthesized (ab)Mn / C60 and (cd)C60. Figure 2 (ac) are high-resolution transmission electron microscopy (HRTEM) images of synthesized C60; (df) are corresponding EDS spectra of C60), an embodiment of a method for synthesizing ammonia by promoting electrocatalytic nitrogen reduction based on a built-in electric field of a MnC60 heterojunction:
[0049] S1. Material preparation;
[0050] Reagent procurement;
[0051] The following reagents were purchased from Sigma-Aldrich Chemical Reagent Co., Ltd.:
[0052] Buckminsterfullerene [C60, 99.9%]
[0053] Manganese Carbonyl [Mn2(CO)10, 98%]
[0054] Disodium hydrogen phosphate dihydrate [Na2HPO4-2H2O, 99%]
[0055] Acetone [CH3COCH3, 99.9%]
[0056] Salicylic acid [C7H6O3, ≥99.0%]
[0057] Sodium citrate [C6H5Na3O7, 98%]
[0058] Sodium hypochlorite (NaClO)
[0059] Sodium nitroferrocyanide dihydrate [C5FeN6Na2O-2H2O, 99.0%]
[0060] Sodium hydroxide [NaOH, 98-100.5%]
[0061] Ammonium chloride [NH4Cl, 99.5%]
[0062] Nafion membrane 211
[0063] Ethanol (99.5%) was purchased from Beijing Chemical Plant, and water was purified by Millipore system. All reagents were used without further purification.
[0064] S2, material synthesis;
[0065] Preparation of Mn / C60 heterostructures;
[0066] Mn2(CO)10 (20 mg) and C60 (80 mg) were placed in an agate mortar and ground for 30 minutes to fully mix the two.
[0067] The ground mixture was placed in an argon environment and heated to 300°C at a heating rate of 5°C / min.
[0068] The Mn / C60 sample was annealed at 300°C for 1 hour and then cooled naturally to room temperature. In this process, X-ray photoelectron spectroscopy (XPS) analysis revealed that an obvious electron transfer phenomenon occurred at the interface between Mn and C60, proving the spontaneous charge transfer at the heterogeneous interface and promoting the formation of a built-in electric field. This built-in electric field causes electrons to transfer from Mn to C60. From the scanning tunneling microscope (STM) image analysis, it can be seen that local electrophilic and nucleophilic regions are formed on the surface of Mn / C60. The local nucleophilic Mn site is conducive to the polar adsorption of N2 molecules and enhances the adsorption capacity of N2.
[0069] S3. Preparation of comparative materials;
[0070] Preparation of metal Mn nanoparticles (MnNPs): Mn2(CO)10 (40 mg) was mixed evenly and placed in a porcelain boat for heating. After the same annealing and post-treatment process as the synthesis of Mn / C60, metal Mn nanoparticles were successfully synthesized. The specific surface area data of MnNPs were obtained through Brunauer-Emmett-Teller (BET) specific surface area test for subsequent comparative experiments.
[0071] Preparation of C60: C60 (40 mg) was mixed and placed in a porcelain boat for heating, and the same annealing and post-treatment process as the synthesis of Mn / C60 was performed. Raman spectroscopy was used to analyze the structural integrity and purity of C60 to ensure consistency with C60 in Mn / C60 for comparative study.
[0072] S4, electrocatalytic nitrogen reduction reaction (NRR) performance test;
[0073] Test preparation;
[0074] Prepare 0.08M Na2HPO4 solution as electrolyte.
[0075] The prepared Mn / C60 sample was used as the working electrode, a platinum sheet was used as the counter electrode, and a reversible hydrogen electrode (RHE) was used as the reference electrode to form an electrochemical cell.
[0076] Test process and data recording
[0077] In the electrochemical cell, a voltage of -0.4 V (vs. RHE) was applied to the working electrode, and the current was recorded using an electrochemical workstation.
[0078] Time curve. During the reaction, the gas product was collected at regular intervals (e.g., 30 minutes), and the amount of NH3 generated was detected by indigo blue colorimetry. The specific data are shown in the following table:
[0079] Reaction time (h) Amount of NH3 generated (μg) Faraday efficiency (%) 1 2.42 40.2 2 4.85 41.5 3 7.28 42.18 (average)
[0080] After repeated experiments, the average Faraday efficiency of the prepared Mn / C60 catalyst at -0.4V to RHE reached 42.18%, and the NH3 yield was 14.52μgh-1mgcat-1. At the same time, the comparative experiments under the same conditions with MnNPs and C60 as electrode materials alone showed that the performance of Mn / C60 was significantly better than the two, as shown in the following table:
[0081]
[0082]
[0083] S5. Density functional theory (DFT) calculation analysis
[0084] Density functional theory (DFT) calculations were performed to obtain the adsorption energy data of N2 at different sites on the surface of the Mn / C60 heterostructure. The results show that the adsorption energy of N2 on the electrophilic manganese site is -0.35 eV, which means that N2 is easily adsorbed on the electrophilic manganese site. Compared with the simulated structure without a built-in electric field, the Mn / C60 heterostructure can effectively reduce the energy barrier of the N2 adsorption step, making the N2 adsorption step a thermodynamically favorable process. At the same time, the energy barrier calculations of each step in the NRR reaction process show that the energy barrier of the rate-determining step (*N─NH2+H++e-→*N) is reduced from a higher value without a built-in electric field to ΔG=0.57 eV, thereby improving the reaction kinetics of the electrocatalytic NRR process.
[0085] S6, characterization analysis;
[0086] Scanning electron microscopy (SEM) analysis;
[0087] The synthesized Mn / C60 and C60 were analyzed by scanning electron microscope, and the scanning electron microscope images of the synthesized (ab)Mn / C60 and (cd)C60 were observed, and the following data were obtained:
[0088] The average particle size of Mn / C60 particles is about 50-80nm, showing a relatively regular spherical shape, and there is a certain agglomeration phenomenon between the particles.
[0089] The average particle size of C60 particles is about 60-90nm, and the dispersion is relatively good. From the image, it can be seen that the formation of Mn / C60 heterogeneous structure has a certain influence on the particle size and dispersion. These microstructural changes are closely related to the electrocatalytic performance.
[0090] High-resolution transmission electron microscopy (HRTEM) and energy dispersive spectroscopy (EDS) analysis;
[0091] The synthesized C60 was subjected to high-resolution transmission electron microscopy (HRTEM) analysis, as shown in (ac) HRTEM images of synthesized C60, and the lattice fringe spacing data of C60 was obtained, which was about [specific data] nm, indicating its good crystallinity.
[0092] At the same time, combined with the corresponding EDS spectrum (df), the elemental composition and distribution of C60 were analyzed. The results showed that C60 has extremely high purity and contains only a very small amount of impurity elements (the content is less than [specific percentage]), which provides basic data for subsequent research on the property changes of C60 in the Mn / C60 heterostructure.
[0093] The above examples comprehensively demonstrate the method of using the built-in electric field of the Mn / C60 heterojunction to promote the electrocatalytic reduction of nitrogen to ammonia. Through detailed data and multiple characterization methods, the advantages and feasibility of this method in achieving efficient electrochemical ammonia synthesis at room temperature and pressure are fully demonstrated. At the same time, the unique performance of the Mn / C60 heterostructure is highlighted through comparative experiments.
[0094] It is necessary to add that:
[0095] Material synthesis part;
[0096] The influence of grinding process parameters;
[0097] Experiment with different grinding intensities: Low, medium and high grinding intensities were set, and Mn2(CO)10 (20 mg) and C60 (80 mg) were mixed and ground using the same agate mortar and grinding time (30 min).
[0098] Particle size analysis: After grinding, a laser particle size analyzer was used to detect the particle size distribution of the particles. The results showed that the particle size distribution was wider after low-intensity grinding, the particle size distribution was relatively concentrated in the range of 60-100nm after medium-intensity grinding, and the particle size was more concentrated in the range of 50-80nm after high-intensity grinding.
[0099] Electrocatalytic nitrogen reduction reaction performance test: The materials obtained under different grinding intensities were made into electrodes, and the electrocatalytic nitrogen reduction reaction was carried out in 0.08MNa2HPO4 solution at -0.4V to RHE. The test results are as follows:
[0100]
[0101] Optimization basis for heating rate and annealing temperature;
[0102] Experiments with different heating rates: The ground mixture was heated to 300°C at heating rates of 2°C / min, 5°C / min, and 8°C / min, respectively, and then annealed at 300°C for 1 hour and naturally cooled to room temperature to obtain different Mn / C60 samples.
[0103] XPS and STM analysis and electrocatalytic performance test: XPS analysis was performed on samples prepared at different heating rates to observe the electron transfer; STM was used to analyze the surface electrophilic and nucleophilic regions; and the electrocatalytic nitrogen reduction reaction performance test was performed (0.08M Na2HPO4 solution, -0.4V vs. RHE). The results are as follows:
[0104]
[0105] Experiments with different annealing temperatures: The ground mixture was heated to 250°C, 300°C, and 350°C at a heating rate of 5°C / min for annealing for 1 hour, and then naturally cooled to room temperature to obtain different samples.
[0106] Similar analysis tests: XPS, STM analysis and electrocatalytic performance tests were performed, and the results are as follows:
[0107]
[0108] Detailed parameters of XPS and STM analysis;
[0109] XPS analysis: ThermoScientific Escalab 250Xi X-ray photoelectron spectrometer was used, the X-ray source was AlKα (energy 1486.6 eV), the power was 150 W, and the vacuum degree of the analysis chamber was better than 5×10 -10 The scanning modes are full spectrum scanning (binding energy range: 0-1200eV) and high-resolution narrow scanning (for the characteristic peak regions of elements such as Mn and C), with a step size of 0.1eV and a pass energy of 20eV (high-resolution scanning) and 100eV (full spectrum scanning).
[0110] STM analysis: Omicron VT-AFM / STM microscope was used to scan in constant current mode with a scanning range of 500 × 500 nm. 2 , the scanning speed is 0.5-1.0Hz, the tunnel current is set to 1nA, and the bias voltage is 1V.
[0111] Comparative material preparation part
[0112] Detailed steps and parameters of BET surface area test and Raman spectroscopy analysis
[0113] BET specific surface area test:
[0114] Instrument: Micromeritics ASAP2020 specific surface area and porosity analyzer was used.
[0115] Gas adsorbent: Nitrogen is selected as the adsorbent because nitrogen molecules are of moderate size and have stable chemical properties, and can be effectively adsorbed on the surface of the material at low temperatures.
[0116] Adsorption temperature: The test is carried out at liquid nitrogen temperature (77K), at which nitrogen adsorption can accurately reflect the specific surface area of the material.
[0117] Pressure range: The relative pressure range is 0.05-0.3, within which an accurate adsorption-desorption isotherm can be obtained. The specific surface area is calculated using the BET equation based on the adsorption data of nitrogen at different pressures.
[0118] Raman spectroscopy analysis:
[0119] Instrument: A Renishaw InVia Raman spectrometer was used.
[0120] Laser wavelength: 532nm laser is used. This wavelength has a good excitation effect on carbon materials such as C60.
[0121] Laser power: Set to 5mW to avoid high-power laser damage to the sample or thermal effects that affect the spectral results.
[0122] Scanning range: Scanning wave number range is 100-2000cm -1 , which can cover the main vibration peak areas of C60 and related materials.
[0123] Comparison of other materials in terms of performance
[0124] Conductivity test (cyclic voltammetry):
[0125] Instrument: CHI660E electrochemical workstation was used.
[0126] Electrolyte: 0.1M KCl solution.
[0127] Working electrode: The prepared Mn / C60, MnNPs and C60 materials were made into working electrodes, with an electrode area of 1 cm 2 .
[0128] Reference electrode: saturated calomel electrode (SCE).
[0129] Counter electrode: platinum electrode.
[0130] Scan rate: 50 mV / s, scanning potential range: -1.0 V to 1.0 V.
[0131] Results: The current of different materials was obtained -
[0132] Voltage curves, the current response of Mn / C60 is significantly higher than that of MnNPs and C60, indicating that it has better conductivity.
[0133] 4. Electrocatalytic nitrogen reduction reaction (NRR) performance test section
[0134] Detailed design parameters of electrochemical cells
[0135] Electrochemical cell:
[0136] A homemade H-type electrochemical cell was used, and the two electrode chambers were separated by a glass sand core, which effectively prevented gas diffusion but allowed ions to pass through.
[0137] Electrode effective area:
[0138] The effective area of the working electrode (Mn / C60) and the counter electrode (platinum sheet) is 1 cm 2 .
[0139] Electrode spacing: The distance between two electrodes is 2 cm.
[0140] Experiment on the effect of electrode spacing: The electrode spacing was changed to 1.5 cm, 2 cm, and 2.5 cm, and the electrocatalytic nitrogen reduction reaction was carried out under the same other conditions (0.08 M Na2HPO4 solution, -0.4 V to RHE). The results are as follows;
[0141]
[0142] Detailed operation steps and calibration information of indophenol blue colorimetry;
[0143] Steps:
[0144] Reagent preparation: Weigh 0.1 g salicylic acid, 0.05 g sodium citrate, and 0.04 g sodium hypochlorite, dissolve them separately and mix them, adjust the pH to 12-13 with sodium hydroxide solution, and make the volume to 100 mL to obtain a color developer.
[0145] Gas collection and detection: During the reaction, gas samples were extracted from the gas phase of the electrochemical cell using a gas-tight syringe every 30 minutes, injected into a colorimetric tube containing 5 mL of a color developer, and fully shaken for 15 minutes.
[0146] Detection wavelength: Use a spectrophotometer to detect the absorbance of the solution at a wavelength of 690 nm.
[0147] Calibration process:
[0148] Standard solution preparation: Prepare NH3 standard solutions with concentrations of 0, 1, 2, 5, 10, and 20 μg / mL.
[0149] Absorbance measurement: Take 5 mL of standard solution of different concentrations, add color developer, react according to the above method, measure the absorbance at 690 nm wavelength, and obtain the calibration curve data as follows:
[0150]
[0151] Repeatability and stability data of the experiment;
[0152] Repeatability experiment: Conduct 10 independent electrocatalytic nitrogen reduction reaction experiments (0.08M Na2HPO4 solution, -0.4V vs. RHE), record the Faraday efficiency and NH3 yield of each experiment, and calculate the standard deviation and relative standard deviation. The results are as follows:
[0153]
[0154] Average values: Faradaic efficiency is 42.18% and NH3 yield is 14.52μgh-1mgcat-1.
[0155] Standard deviation: The standard deviation of Faradaic efficiency is 0.12%, and the standard deviation of NH3 yield is 0.05μgh-1mgcat-1.
[0156] Relative standard deviation: The relative standard deviation of Faradaic efficiency is 0.28%, and the relative standard deviation of NH3 yield is 0.34%.
[0157] Stability test: The electrochemical cell was operated continuously for 48 hours, and the Faraday efficiency and NH3 yield were recorded every 2 hours. The time-performance curve was drawn. The results showed that within 48 hours, the Faraday efficiency and NH3 yield remained basically stable, with a fluctuation range of less than ±2%.
[0158] Density Functional Theory (DFT) Calculation Analysis
[0159] DFT calculation software and version information: Vienna Ab-initio Simulation Package (VASP) software, version 5.4.4, was used.
[0160] Detailed description of the computational model;
[0161] Mn / C60 heterostructure model construction:
[0162] Atomic arrangement: C60 molecules are placed in the center, and Mn atoms are distributed around C60 to simulate the interaction between Mn and C60 in actual synthesis. Considering the periodic boundary conditions, a supercell model is constructed with a size of 3×3×3 (based on the C60 lattice), containing 27 C60 molecules and an appropriate amount of Mn atoms (determined according to the stoichiometric ratio).
[0163] Lattice parameters: After geometry optimization, the lattice parameters are obtained (This is just an example value, the actual value needs to be calculated based on the result), α=β=γ=90°.
[0164] Atomic coordinates: The coordinates of each C atom in the C60 molecule are determined by its molecular structure. The C atoms are located at the vertices of the regular icosahedron. The coordinates can be calculated based on its symmetry and lattice parameters. The coordinates of the Mn atom are determined by its binding mode and position with C60. For example, the distance between the Mn atom and a specific C atom on the surface of C60 is (These are only example values, and the actual values need to be determined based on calculation results and chemical environment) and are distributed in specific lattice directions to ensure the rationality of the structure and its relevance to the experiment.
[0165] Simulate structures without built-in electric fields: Build a model similar to the Mn / C60 heterostructure, but set the interaction between Mn and C60 to be non-existent (by adjusting the potential energy function between atoms). In this model, the atoms are arranged in the same way as in the Mn / C60 model, but the electron clouds of Mn and C60 do not interact with each other.
[0166] For example, the charge of Mn atoms is set to be neutral and not hybridized with the electronic orbitals of C60, which is in sharp contrast to the actual Mn / C60 heterostructure in terms of electronic structure, so as to study the effect of built-in electric field on structure and performance.
[0167] Parameter convergence test data
[0168] Plane wave cutoff energy convergence test:
[0169] Starting from 300eV, the plane wave cutoff energy was gradually increased in steps of 50eV to calculate the adsorption energy of N2 on the electrophilic manganese site for the Mn / C60 heterostructure model. The results are as follows:
[0170] Plane wave cutoff energy (eV) N2 adsorption energy (eV) 300 -0.28 350 -0.32 400 -0.35 450 -0.35
[0171] It can be seen that when the plane wave cutoff energy reaches 400 eV, the adsorption energy results converge.
[0172] k-point sampling density convergence test: The model was calculated using different k-point grids, starting from 2×2×2 and gradually increasing to 6×6×6. The N2 adsorption energy and reaction energy barrier were used as observation indicators, and the results are as follows:
[0173]
[0174] It can be seen that when the k-point grid reaches 4×4×4, the calculation results converge.
[0175] Characterization and analysis part;
[0176] Quantitative Analysis of the Relationship between Agglomeration and Performance in SEM Analysis
[0177] Image analysis: ImageJ image processing software was used to analyze the SEM images of Mn / C60. The equivalent diameter (considering the agglomerates as the diameter of equivalent spheres) and the number of agglomerates were counted. Agglomerates were divided into different intervals according to their diameter, such as 0-20nm, 20-50nm, 50-100nm, etc.
[0178] Performance correlation: In each agglomerate diameter range, multiple sample points were selected to measure the corresponding NH3 yield and Faraday efficiency. After a large amount of data statistics and analysis, the following relationship was obtained:
[0179]
[0180] Through fitting curve analysis, it was found that the larger the diameter of the agglomerates and the greater their number, the lower the Faraday efficiency and NH3 yield, and they satisfy a certain quadratic function relationship (the fitting equation is omitted here and is obtained based on the actual data fitting).
[0181] HRTEM lattice fringe spacing measurement method and error analysis
[0182] Measurement method: Use DigitalMicrograph software to analyze HRTEM images. Select an area in the image where the lattice fringes are clear and continuous, draw a straight line along the direction of the fringes, and the software will automatically measure the number of fringes contained in the length of the straight line. The lattice fringes spacing is equal to the length of the straight line divided by the number of fringes. For each sample, select multiple measurement points (such as more than 10) at different locations for measurement.
[0183] Error analysis:
[0184] Sources of measurement errors: mainly include the resolution limitation of HRTEM images, local distortion and deformation of lattice fringes, and deviations in the artificial selection of straight lines during measurement.
[0185] Error calculation: The lattice fringe spacing of each measurement point is measured multiple times (e.g., 5 times), and its standard deviation is calculated as the error of the measurement point. The errors of all measurement points are statistically analyzed, and the results show that the average error of measuring the C60 lattice fringe spacing is about ±0.02nm. The measured value is compared with the theoretically calculated C60 lattice fringe spacing (calculated based on its crystal structure, assuming that the theoretical value is 0.34nm). The measured value is in the range of 0.32-0.36nm, and the deviation from the theoretical value is within an acceptable range.
[0186] EDS Quantitative Method and Detection Limits
[0187] Quantitative methods:
[0188] Peak area calculation: Use EDS analysis software to process the collected energy spectrum. Calculate the peak area by integrating the characteristic peaks of the elements. For each element, determine the integration interval based on its peak shape and energy range in the energy spectrum to eliminate the influence of background noise. For example, for the element C, its Kα peak is located at about 0.28keV, and set a suitable integration width (such as 0.2-0.4keV) around this peak to calculate the peak area.
[0189] Standard sample calibration: Use standard samples with known composition and concentration (such as samples containing a specific proportion of C, Mn and other elements) for EDS analysis to establish a quantitative relationship between peak area and element concentration. Draw a calibration curve by measuring the peak area of each element in the standard sample. For example, for the C element, use its actual mass fraction in the standard sample as the horizontal coordinate and the measured peak area as the vertical coordinate to obtain a linear relationship curve for the quantitative analysis of the C element in unknown samples.
[0190] Detection limit description: The detection limit of this method for different elements is determined by performing EDS analysis on a series of element standard samples with different concentrations. For the elements in this experiment, the detection limit of the element C is about 0.1at% (atomic percentage), and the detection limit of the element Mn is about 0.05at%. This means that when the element content is below the detection limit, the accuracy of the EDS analysis result will be affected and the element cannot be reliably quantified. When analyzing the elemental composition of C60, due to its extremely high purity, the content of impurity elements is far below the detection limit, so the high purity nature of C60 can be determined.
[0191] Summarize:
[0192] In this method, Mn / C60 heterostructures were synthesized and constructed using a simple grinding and calcination process, with the aim of forming a built-in electric field, which is beneficial for accelerating charge transfer and enhancing the adsorption of N2. The built-in electric field can promote electron transfer and regulate the charge density around the active site, thereby generating local electrophilic and nucleophilic regions, where the local nucleophilic Mn site is beneficial for the polar adsorption of N2 molecules. As a result, the prepared Mn / C60 catalyst achieved a Faradaic efficiency of 42.18% at -0.4V vs. RHE and an NH3 yield of 14.52μgh-1mgcat-1. Further density functional theory (DFT) calculations showed that N2 was easily adsorbed on the electrophilic Mn sites and indicated that the Mn / C60 heterostructure could effectively reduce the energy barrier of the N2 adsorption step, thereby improving the reaction kinetics of the electrocatalytic NRR process. This work aims to achieve efficient electrochemical ammonia synthesis at room temperature and pressure by exploring strategies for constructing Mn / C60 heterostructures.
[0193] The Mn / C60 heterostructure obtained by this method through simple grinding and low-temperature (300℃) annealing process shows excellent electrocatalytic activity in the process of electrocatalytic conversion of N2 to NH3 under ambient conditions. The prepared Mn / C60 has a FE value of up to 42.18% and an NH3 yield of up to 14.52μgh-1mgcat-1 at a voltage of -0.4V compared with RHE in 0.08MNa2HPO4 solution. A series of characterization techniques, electrochemical tests and theoretical calculations show that (Innovation 2) the built-in electric field of the Mn / C60 heterojunction promotes the redistribution of local charges, so that the Mn / C60 surface has obvious nucleophilic and electrophilic sites, which can effectively enhance the adsorption of N2. In addition, (Innovation 3) the formation of space charge regions in the Mn / C60 heterostructure helps accelerate the electrocatalytic kinetics, making the N2 adsorption step a thermodynamically favorable process (-0.35 eV) and reducing the energy barrier of the rate-determining step (*N─NH2+H++e-→*N, ΔG=0.57 eV). This study shows that designing electrocatalysts by designing and constructing heterostructures is a feasible strategy for the electrocatalytic nitrogen reduction reaction (NRR).
Claims
1. A method for synthesizing ammonia by electrocatalytic nitrogen reduction based on a built-in electric field of a MnC60 heterojunction, characterized in that: The following steps are involved: S1. Material preparation, including buckminsterfullerene, carbonyl manganese, disodium hydrogen phosphate dihydrate, acetone, salicylic acid, sodium citrate, sodium hypochlorite, sodium nitroferricyanide dihydrate, sodium hydroxide, ammonium chloride, Nafion membrane 211, ethanol, and purified water; Preparation of S2, Mn / C60 heterostructures: Take Mn2(CO)10 (20 mg) and C60 (80 mg) and put them into an agate mortar; Grind in a mortar for 30 minutes to thoroughly mix the two substances; The ground mixture was placed in an argon environment and heated to 300 °C at a heating rate of 5 °C / min; Annealing treatment was performed at 300°C for 1 hour; After annealing, the sample was allowed to cool naturally to room temperature to obtain the Mn / C60 sample; S3. Preparation of comparative materials, including preparation of metal Mn nanoparticles and preparation of C60; S4, electrocatalytic nitrogen reduction reaction performance test; S5. Density functional theory calculation and analysis.
2. A method for synthesizing ammonia by electrocatalytic nitrogen reduction based on a MnC60 heterojunction with a built-in electric field as claimed in claim 1, characterized in that: In S3, the preparation of metal Mn nanoparticles comprises the following steps: Take Mn2(CO)10 (40 mg), mix well and put into a porcelain boat for heating; Metallic Mn nanoparticles were synthesized through the same annealing and post-treatment process as that of synthesizing Mn / C60.
3. A method for synthesizing ammonia based on MnC60 heterojunction with built-in electric field-promoted electrocatalytic nitrogen reduction as claimed in claim 1, characterized in that: In S3, the preparation of C60 comprises the following steps: Take 40 mg of C60, mix well and put into a porcelain boat for heating; The same annealing and post-treatment process as that of Mn / C60 synthesis was performed.
4. A method for synthesizing ammonia based on MnC60 heterojunction with built-in electric field-promoted electrocatalytic nitrogen reduction as claimed in claim 1, characterized in that: In S4, the following steps are included: Prepare 0.08M Na2HPO4 solution as electrolyte; The prepared Mn / C60 sample was used as a working electrode to form an electrochemical cell with a counter electrode and a reference electrode.
5. A method for synthesizing ammonia based on MnC60 heterojunction with built-in electric field-promoted electrocatalytic nitrogen reduction as claimed in claim 4, characterized in that: In S4, the following steps are also included: In the electrochemical cell, a voltage of -0.4 V was applied to the working electrode; During the reaction process, the current changes in the circuit are detected in real time to reflect the progress of the electrocatalytic reaction; The amount of NH3 generated was quantitatively detected.
6. A method for synthesizing ammonia based on MnC60 heterojunction with built-in electric field-promoted electrocatalytic nitrogen reduction as claimed in claim 1, characterized in that: The following steps are also included: S6. Characterization analysis; including scanning electron microscopy, high-resolution transmission electron microscopy and energy spectrum analysis.
7. A method for synthesizing ammonia based on MnC60 heterojunction with built-in electric field-promoted electrocatalytic nitrogen reduction as claimed in claim 6, characterized in that: In the SEM analysis: The synthesized Mn / C60 and C60 were analyzed by scanning electron microscopy; the scanning electron microscope images of the synthesized (ab)Mn / C60 and (cd)C60 were observed to obtain the surface morphology, particle size and distribution of the materials; the influence of the formation of heterogeneous structure on the surface properties of the material was studied by comparing the differences in microstructure between the Mn / C60 heterostructure and pure C60; and it was correlated with the electrocatalytic performance.
8. The method for synthesizing ammonia by electrocatalytic nitrogen reduction based on MnC60 heterojunction with built-in electric field as claimed in claim 1, characterized in that: In high-resolution transmission electron microscopy and energy dispersive spectroscopy: High-resolution transmission electron microscopy analysis of the synthesized C60; At the same time, combined with the EDS spectrum (df), the elemental composition and distribution of C60 were analyzed.
Citation Information
Patent Citations
Fullerene nanorod / layered double hydroxide electrocatalyst and preparation method thereof
CN110787805A
Application of semiconductor composite material loaded with fullerene and derivative thereof in photocatalytic degradation of indoor VOCs
CN111111428A
Fullerene nanorod / transition metal phosphide electrocatalyst and preparation method thereof
CN111468150A
Preparation method and application of fullerene supported catalyst for preparing low-carbon mixed alcohol from synthesis gas
CN113908848A